2019
DOI: 10.3892/mco.2019.1875
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy with trastuzumab for epidermal growth factor receptor 2 (HER2)‑positive advanced salivary duct carcinoma: A case report

Abstract: Herein we report two cases of advanced and/or metastatic salivary duct carcinoma that relapsed after standard first-line chemotherapy. As overexpression of human epidermal growth factor receptor 2 (HER2) (3+) was observed by immunohistochemistry, the patients were treated with trastuzumab plus paclitaxel. One patient showed a complete response lasting over 2.5 years after the commencement of therapy; however, the other patient had no response to trastuzumab combined therapy. Dual fluorescence in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In case reports, a total of twelve patients received a combination of trastuzumab with docetaxel/paclitaxel [22][23][24]27,30,34,38,48,56]. Two patients had CR (17%) and eight patients had PR (67%).…”
Section: Her2 Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In case reports, a total of twelve patients received a combination of trastuzumab with docetaxel/paclitaxel [22][23][24]27,30,34,38,48,56]. Two patients had CR (17%) and eight patients had PR (67%).…”
Section: Her2 Targeted Therapymentioning
confidence: 99%
“…Additional SDC case reports mentioned the effect of different combinations of chemotherapy in seven patients [24,30,43,48,61]. Three out of these seven patients had PR (one on CAP, one with cisplatin + vinorelbine, one with cisplatin + docetaxel).…”
Section: Chemotherapymentioning
confidence: 99%
“…Human epidermal growth factor receptor 2 is a member of the human epidermal growth factor receptor family and is associated with a poor prognosis in breast carcinomas. 20,21 Overexpression of HER2 is also common in salivary gland cancers and is generally associated with a poor prognosis and aggressive tumor behavior. 22,23 In our study, HER2 was found to be positive in 28% of the patients with malignant SGTs, but there was no correlation between HER2 expression and RANK and RANKL expression.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, more information is gathered about possible molecular targets for a tailored therapy for SGCs [19,20]. Promising results have been achieved with, for example, Herceptin and NTRK inhibitors in selected patients with primarily unresectable disease [10,21,22].…”
Section: Introductionmentioning
confidence: 99%